Mediation of Cognitive Function Improvements by Strength Gains After Resistance Training in Older Adults with Mild Cognitive Impairment: Outcomes of the Study of Mental and Resistance Training. Issue 3 (24th October 2016) - Mavros, Yorgi; Gates, Nicola; Wilson, Guy C.; Jain, Nidhi; Meiklejohn, Jacinda; Brodaty, Henry; Wen, Wei; Singh, Nalin; Baune, Bernhard T.; Suo, Chao; Baker, Michael K.; Foroughi, Nasim; et al.
Abstract : Objectives: To determine whether improvements in aerobic capacity (VO2peak ) and strength after progressive resistance training (PRT) mediate improvements in cognitive function. Design: Randomized, double‐blind, double‐sham, controlled trial. Setting: University research facility. Participants: Community‐dwelling older adults (aged ≥55) with mild cognitive impairment (MCI) (N = 100). Intervention: PRT and cognitive training (CT), 2 to 3 days per week for 6 months. Measurements: Alzheimer's Disease Assessment Scale–cognitive subscale (ADAS‐Cog); global, executive, and memory domains; peak strength (1 repetition maximum); and VO2peak . Results: PRT increased upper (standardized mean difference (SMD) = 0.69, 95% confidence interval = 0.47, 0.91), lower (SMD = 0.94, 95% CI = 0.69–1.20) and whole‐body (SMD = 0.84, 95% CI = 0.62–1.05) strength and percentage change in VO2peak (8.0%, 95% CI = 2.2–13.8) significantly more than sham exercise. Higher strength scores, but not greater VO2peak, were significantly associated with improvements in cognition ( P < .05). Greater lower body strength significantly mediated the effect of PRT on ADAS‐Cog improvements (indirect effect: β = −0.64, 95% CI = −1.38 to −0.004; direct effect: β = −0.37, 95% CI = −1.51–0.78) and global domain (indirect effect: β = 0.12, 95% CI = 0.02–0.22; direct effect: β = −0.003, 95% CI = −0.17–0.16) but not for executive domain (indirect effect: β = 0.11, 95% CI = −0.04–0.26; direct effect: β = 0.03, 95% CI = −0.17–0.23). Conclusion: High‐intensity PRT results in significant improvements in cognitive function, muscle strength, and aerobic capacity in older adults with MCI. Strength gains, but not aerobic capacity changes, mediate the cognitive benefits of PRT. Future investigations are warranted to determine the physiological mechanisms linking strength gains and cognitive benefits.